IMPLEMENTASI MAṢLAḤAH DALAM KEGIATAN EKONOMI SYARIAH - FAHLEFI, RIZAL (JURIS (Jurnal Ilmiah Syariah), 2015)
In terms of Islamic laws, anything that concern with faith (aqidah), worship (‘ibadah) dan deed (muamalah) are basically aimed at ensuring safety in the world and hereafter as well. maslahah  is the most important concept in developing economy and the principles of maslahah  in economic field have been taken as guidance in order to achieve maqasid syariah. Obeying sharia laws is the way to realize maslahah . The implementation of maslahah in economy can be viewed from various activities of mankind in carrying out practices in economy which develop continuously and innovatively, such as in market mechanism, establishment of hisbah institution, productive divine tax (zakat), the presence of sharia financial institution, and so forth.Kata kunci: maṣlaḥah, maqāṣid syarī‘ah, implementasi